Strategies for Energy and Climate Management at the British Columbia Institute of Technology - Moore, Jennie (Universitas Diponegoro, 2021)
The British Columbia Institute of Technology (BCIT) is Canada's premier polytechnic. In 2008, BCIT partnered with its local electricity utility to hire a full-time energy manager. The following year, BCIT's School of Construction and the Environment initiated a campus-as-living-lab of sustainability project called Factor Four in the seven buildings it occupies on BCIT's main campus in Burnaby. The purpose was to explore whether a four-fold (75%) reduction in materials and energy use could be achieved without compromising service levels. By 2016, the project achieved a 50% reduction in energy use and associated greenhouse gas emissions. Factor Four attracted over four million dollars in funding, engaged over 250 students from 12 educational programs, and produced over 200,000 savings annually. In 2017, BCIT set an ambitious target to reduce its annual greenhouse gas emissions 33% below 2007 levels by 2023, and 80% by 2050, across all five of its campuses. BCIT’s ultimate goal is to become both greenhouse gas neutral and a net energy producer. By setting ambitious targets and systematically implementing energy efficiency improvements, utilizing waste-heat exchange, fuel switching, and developing on-site renewable energy, BCIT is on track to achieving its energy management and climate change goals.